Comparison of the performance of MR-deDuster with other conventional cyclones - Rashid, M.; Huda, N.; Norelyza, H.; Hasyimah, N. (Universiti Kebangsaan Malaysia, 2015)
A new type of cyclone design configuration called MR-deDuster, which contains multi cyclone, has been developed. A theoretical study had been carried out to evaluate and predict the performance of a MR-deDuster. In this paper, a comparative study was done to investigate the performance of MR-deDuster with other conventional cyclones in terms of collection efficiency and pressure drop. The performance of MR-deDuster was measured by its collection efficiency based on the particle size distribution of activated carbon. It was found that MR-deDuster is able to collect as high as 94% of PM10 which is high comparing with many other conventional cyclones. In addition, the pressure drop of the unit is relatively low compared to the other cyclones which highlight the ability of the unit to capture the fine particle at low pressure drop.